SELEKSI JAMUR PATOGEN SERANGGA Beauveria spp. SERTA UJI PATOGENISITASNYA PADA SERANGGA INANG-WALANG (Leptocorisa acuta) - Wartono Wartono; Cyntia Nirmalasari; Yadi Suryadi (BERITA BIOLOGI, 2016)
Rice-stink bug (Leptocorisa acuta Thumb) that attack rice crop often causing heavy damage of panicle of rice as well as decreasing either quantity or quality of grain after harvest. The objective of this research was to select 14 entomopatogenic fungi of Beauveria spp. isolates, collected from rice stink bug (L. acuta) and their pathogenicity assay to insect host L. acuta. We also aimed to study diversity of Beuveria spp. which was isolated from insect host from Situgede, Bogor. The research was conducted at Laboratory, and Green house of Center for Agricultural Biotechnology and Genetic Resources Research and Development, Bogor, in 2014. Result of the study showed that isolates from Situgede Bogor were sucessfully isolated  as Beauveria spp. based on Koch Postulat assay.  The identified fourteen isolates were morphologically confirmed as Beauveria spp. The pathogenicity test was indicated by symptoms and mortality of rice stink bug after inoculation with these entomopathogenic fungi. The Beuveria isolates Stgd2(14)1, Stgd6(14)1, Stgd7(14)2, Stgd8(14)2, and Stgd0113 were the most virulent isolates. Stgd2(14)1 provided the fastest time to kill L. acuta with LT50 values of 6.9 days. The 13 isolates of Beauveria were well amplified by ITS primers. However, no diversity was found among isolates, presumably due its narrow host range tested.